Acute limb ischemia in COVID-19 patients: an overview - Abood, Hashem Bark; Alsaedi, Wael Hamed; Bokhari, Abdulwahab Mohammad; Almughalleq, Ahmad Mohammed; Algethami, Ranin Owaidh; Zaini, Sama Mohammed; Ayoub, Hanin Abdulrahman; Baamer, Maan Khaled; Alanazi, Wael Hassan; Al Mohammedali, Ahmed Ebraheem; Alghamdi, Zoha Saleh (International Journal Of Community Medicine And Public Health, 2021)
COVID-19 causes a wide range of clinical symptoms. COVID-19 hematologic and cardiovascular involvement induces thromboembolic symptoms in various organs, most notably venous thromboembolism (VTE); peripheral arterial involvement is uncommon. Acute limb ischemia (ALI) is a vascular emergency known as a dramatic drop in arterial perfusion of a limb that poses a challenge to the limb's viability. Given routine need for thromboprophylaxis, hospitalised COVID-19 patients are at an elevated risk of ALI, limb loss, or even mortality. Understanding the various specific symptoms of COVID-19 patients, especially extrapulmonary manifests, is crucial for both better patient care and the development of adequate infection prevention methods. Although ALI is a complication of COVID-19 in hospitalized patients, it is now being understood that it can arise in patients with mild COVID-19 symptoms, and that ALI can be the first presenting sign of COVID-19 even in the absence of respiratory symptoms. It is recommended that acutely admitted COVID-19 cases should be given pharmacologic thromboprophylaxis with low molecular weight heparin (LMWH) or fondaparinux unless there is a chance of bleeding or contraindicated. Anticoagulant treatment, primarily with LMWH, correlates strongly with an improved prognosis in serious COVID-19 patients who follow sepsis-induced coagulopathy requirements or have significantly elevated D-dimer levels.